2019
DOI: 10.1042/bsr20190505
|View full text |Cite
|
Sign up to set email alerts
|

BCYRN1 is correlated with progression and prognosis in gastric cancer

Abstract: Long non-coding RNA brain cytoplasmic RNA 1 (BCYRN1) has been found to play an important role in tumorigenesis of a variety of tumors including gastric cancer (GC). However, the prognostic significance and molecular mechanism of BCYRN1 was still unknown in GC. In the present study, we found BCYRN1 expression was dramatically elevated in GC tissues and cell lines, and positively associated with tumor depth, lymph node metastasis and clinical stage in patients with GC. Moreover, univariate and multivariate Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…BCYRN1, termed as BC200, has been found in a variety of cancers as previous studies. Either as an oncogenic lncRNA or a tumor suppressor, BCYRN1 was reported to exert significant biological function in cancers such as NSCLC, ovarian cancer, and gastric cancer [31,[44][45][46][47][48]. However, as a lncRNA derived from brain cytoplasm, the expression and function of BCYRN1 in glioma remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…BCYRN1, termed as BC200, has been found in a variety of cancers as previous studies. Either as an oncogenic lncRNA or a tumor suppressor, BCYRN1 was reported to exert significant biological function in cancers such as NSCLC, ovarian cancer, and gastric cancer [31,[44][45][46][47][48]. However, as a lncRNA derived from brain cytoplasm, the expression and function of BCYRN1 in glioma remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet known how BC200 RNA enhances the stability of S100A11 mRNA. Additionally, some studies suggest that BC200 RNA may promote the development of cancer cells by inhibiting tumor-suppressive miRNAs [84,85].…”
Section: Bc Rnas In Cancersmentioning
confidence: 99%
“…BCYRN1 is a brain cytoplasmic lncRNA that is newly identified and activated by c-MYC [15]. It has been reported that BCYRN1 is highly expressed in various tumour tissues [16], such as hepatocellular carcinoma [17], gastric cancer [18], and lung cancer [15] but is expressed at lower levels in healthy control (HC) tissues. In addition, BCYRN1 plays an important role in inhibiting smooth muscle differentiation and vascular development in the cardiovascular system [19,20].…”
Section: Introductionmentioning
confidence: 99%